Florida H2OSAV Insights: Home Water Use in the Gainesville Regional Utilities (GRU) Service Territory - Nick Taylor; Kaitlin Olander Robb Price; Bradley C. Spatz; Tricia E. Kyzar; Pierce Jones (EDIS)
This 6-page fact sheet discusses basics about water consumption for single-family, detached homes served by Gainesville Regional Utilities, information about the highest water users, and impacts of irrigation on water consumption. Written by Nick Taylor, Kaitlin Olander Robb Price, Bradley Spatz, Tricia Kyzar, and Pierce Jones, and published by the UF/IFAS Department of Agricultural and Biological Engineering, September 2020.